"Split-day syndrome", a patient with frontotemporal dementia who lives two days in the span of one: a case report and review of articles. Issue 3 (4th May 2022) - Pourriyahi, Homa; Almasi-Dooghaee, Mostafa; Imani, Atefeh; Vahedi, Taravat; Zamani, Babak
ABSTRACT: Frontotemporal dementia (FTD) is among the most prevalent causes of young-onset dementia  . Along with the frontotemporal and striate atrophy, dopamine dysregulation is also present in FTD. The dopamine system controls mechanisms of time perception. Its depletion can cause miscalculations in the perception of time. We present a 72-year-old man with a unique profile of disorientation in time, such that he split each day into two, 12-h intervals. Although through each 12-h period, he went by his daily activities as if a complete day had passed, e.g., he had two sets of breakfast, lunch, and dinner  , hence the designated "split-day syndrome."